Pelatihan Keterampilan Komunikasi Kelompok Sadar Wisata (Pokdarwis) Dalam Mengembangkan Pariwisata di Desa Panji - Luh Gd Rahayu Budiarta (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This community services program aims tofacilitate tourism awareness groups (Pokdarwis) in improving English language skills and the ability to guide tours in Panji Village and increase the tourist attraction in Panji Village by helping the tourism awareness group in making tour packages in the form of brochures. In the current pandemic conditions, tourism in Bali is experiencing a decline in the level of visits due to social restrictions imposed by the Government. Therefore, in order to revive the enthusiasm of tour guides, especially in Panji Village, this training is expected to be able to improve the quality of human resources to be better in preparing for the new normal era. The participatory approach method was used where the participants will later be actively involved in this service activity. This program was implemented succesfully, the participants were very cooperative and active in delivering the material.The results of this program had a positive impact on the participants. It is hoped that in the next, this program can continue to be implemented to monitor the development of English language skills of the participants. Keywords: Tourism awareness group, Tourism, English